Whole mitochondrial genome screening in two families with hearing loss: detection of a novel mutation in the 12S rRNA gene. Issue 6 (24th September 2010) - Mkaouar-Rebai, Emna; Fendri-Kriaa, Nourhene; Louhichi, Nacim; Tlili, Abdelaziz; Triki, Chahnez; Ghorbel, Abdelmoneem; Masmoudi, Saber; Fakhfakh, Faiza
Abstract : Sensorineural hearing loss has been described in association with different mitochondrial multisystemic syndromes, often characterized by an important neuromuscular involvement. Until now, mutations in mitochondrial DNA, especially in the 12S rRNA, the tRNA Ser(UCN) and the tRNA Leu(UUR) genes, were implicated in syndromic or non-syndromic hearing loss either as a primary cause or as predisposing factors. In the present study, we performed a whole mitochondrial genome screening in two unrelated Tunisian families with inherited hearing loss. Results showed the presence of a novel mutation in the mitochondrial 12S rRNA gene in the two probands of these two families who belong to two different haplogroups: L3 and H6a1. The m.735A>G mutation affects a conserved nucleotide of the mitochondrial 12S rRNA gene in primates and other species and had a conservation index of 78.5% (11/14). We also detected known polymorphisms and sic novel mitochondrial variants. The present study confirmed that the mitochondrial 12S rRNA gene is a hot spot for mutations associated with hearing impairment.